INDIGENOUS KNOWLEDGE ON SOME MEDICINAL PLANTS AMONG THE MALAYALI TRIBALS IN YERCAUD HILLS, EASTERN GHATS, SALEM DISTRICT, TAMIL NADU, INDIA. - R. REKKA,; S.SENTHIL KUMAR, (International Journal of Pharma and Bio Sciences, 2014)
The present work was to identify and enumerated some of the plant species used for medicinal purposes by the Malayali tribals of Yercaud Hills, Salem district, Tamil Nadu, India. The study was conducted among the Malayali tribals of Yercaud hills through survey, personal interviews and field visit along with the informants during November 2012 – March 2014. Informants were selected based on their knowledge of medicinal plants. A total of 51 plant species distributed in 50 genera belonging to 38 families used to cure various ailments by Malayali tribals. Traditional healers were using these plants to cure beetle bite, trismus, snake bite, chest pain, dental ache, flatulence, Normal delivers, Paralysis, Migraine, bone fracture, rheumatism, Oligospermia, eczema, cycosis, dysuria, wound healing, piles, Kidney stone, liver disorder and asthma. The present investigation revealed that medicinal plants still play a vital role in the primary health care of the people. The information gathered from tribals is useful for the further research in the field of ethnobotany, taxonomy. This study offers a model for studying the relationship between plants and people and traditional remedies of great therapeutic importance. The value of using ethnobotanical information is to initiate drug discovery efforts. This study also gathered a broad spectrum of information concerning medicinal plants used by tribals.